Learning equation-solving using a technological manipulative and languaging - Lehtonen, Daranee; Joutsenlahti, Jorma (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
Procedural competence traditionally emphasised in school mathematics teaching alone is not sufficient to succeed in learning mathematics. The Finnish National Core Curriculum for Basic Education 2014 has underlined the importance of students’ understanding of mathematical concepts. This article uses Lehtonen’s dissertation to demonstrate how educational technology utilisation can promote students’ mathematical concepts understanding. A multimodal manipulative was developed for primary school students to learn how to solve equations with understanding. The manipulative combines the strengths of physical and digital tools: physical component manipulation helps students focus on their activities; digital components motivate students to learn and provide them with real-time guidance and feedback. Class intervention results reveal that the developed manipulative together with languaging of mathematical thinking helped fourth graders learn key concepts in equation solving. The manipulative functioned as students’ learning, communication, and collaborative tool. Students perceived it as beneficial, easy, and pleasant to use. In the future, they would like to learn mathematics by doing and languaging with peers.